The molecular diagnosis of house dust mite allergy: a short review - Choina, Magdalena; Gromek, Weronika; Wilk, Klaudia; Marzęda, Magdalena; Pukaliak, Roman (Journal of Education, Health and Sport, 2022)
Introduction: House dust mite (HDM) allergens are considered among the most essential elicitors of allergic rhinitis and asthma worldwide [1]. How can we determine the individual sensitization profile of a patient? Is there a way to monitor the development of allergic symptoms? Is it possible to tailor different forms of therapy based on the individual sensitization profile of a patient? Purpose: The study aims to show the benefits of molecular diagnostics of allergies based on the example of HDM allergy. Description of the state of knowledge: Clinical manifestation is the most important aspect of diagnosing HDM allergy. The determination of allergen specific immunoglobulins E (asIgE) against HDM extracts may be helpful in the identification of the cause of allergy symptoms. However, the diagnosis using allergen extracts cannot be established in all cases. What revolutionised the diagnosing process of HDM allergy is the molecular diagnostics of allergy. Based on the presence of asIgE against allergen molecules it is possible to identify the allergen responsible for the sensitisation as well as personalise the therapeutic recommendations. Summary: The molecular diagnostics of allergy significantly improved the specificity and sensitivity of HDM allergy diagnostics. Molecular diagnostics in individuals with HDM allergy make it possible to establish the individual patient’s allergy profile, and consequently personalise therapeutic recommendations. It is especially important regarding the selection of patients who may benefit from immunotherapy. The component-resolved diagnostics in allergology is a step toward personalised medicine.